The Influences of Locus of Control, Debt, and Framing on Retirement Contributions - FOLTICE, Bryan; ILCIN, Patrick (Journal of Advanced Studies in Finance, 2019)
This study evaluates locus of control, debt, and framing effects as potential drivers of retirement savings decisions. We administer an online survey analyzing how much an individual will save for retirement upon graduating college. The study finds that individuals with an external locus of control contribute significantly less to their retirement savings than individuals with an internal locus of control. Interestingly, this study finds no significant relationship between debt overhang and initial contributions. To measure framing effects, participants were given the choice to change their initial contribution rate after seeing the estimated increased future amount of their account balance based on an annual contribution increase for each 1% of salary (percentage frame group) or $500 (dollar frame group). The survey results show that individuals that were given the percentage frame increase their initial contribution to their retirement account significantly more than the group receiving the dollar frame.